Pomegranate: A review of the heavenly healer’s past, present, and future - Mehran Mohammadi; Zahra Boghrati; Seyed Ahmad Emami; Maryam Akaberi (Iranian Journal of Basic Medical Sciences, 2023)
In the great Persian Empire, pomegranate (Punica granatum L.) had a wide reputation for use both as an herbal medicine and nutritious food. It was also a symbol of peace and love according to Achaemenid limestones in the great Persia. This paper aims to review the traditional uses of pomegranate in Persian and Islamic traditional medicine and have thorough and current information regarding the pharmacology and phytochemistry of this valuable plant for practical use and further research. Relevant information about P. granatum was collected from scientific publishers and databases including Elsevier, Wiley, PubMed, and Google Scholar between 1950 and 2022. The traditional knowledge was extracted from Persian and Islamic traditional textbooks. Based on traditional textbooks, pomegranate has beneficial effects on diseases related to gastrointestinal, upper and lower respiratory, visual, and reproductive systems. In addition, pomegranate and its preparations have been prescribed for treating metabolic disorders, skin problems, and wounds as well as dental protection. Preclinical and clinical evidence supports many therapeutic potentials of pomegranate in traditional medicine. Its therapeutic effects are mostly attributed to its polyphenols. The knowledge in Persian and Islamic traditional textbooks about pomegranate and its preparations can be used as a guide for further preclinical and mainly clinical studies to discover the therapeutic potential of this valuable plant.